School Adjustment of Children with and without Special Needs in Preschool Classrooms - Hatice Bakkaloğlu; Bülbin Sucuoğlu (Elementary Education Online, 2023)
This study was conducted to adapt and examine the psychometric properties of a measurement tool into Turkish that can be used to assess school adjustment of children with and without special needs and to determine whether school adjustment of children differ according to gender and having special needs or not. A total of 22 preschool teachers and 22 children with special needs as well as 235 children without special needs totaling 257 children participated in this study. Data were collected by an Information Form and Short Form of the Teacher Rating Scale of School Adjustment (SF-TRSSA). The findings show that SF-TRSSA is a valid and reliable assessment tool. Moreover, gender and having special needs significantly affect scores of children on SF-TRSSA, i.e., girls have higher scores than boys and children with special needs have lower scores than their peers without special needs. The findings are discussed in line with the literature.